2022
DOI: 10.1155/2022/1030238
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Alleviates Pulmonary Fibrosis by Promoting Autophagy via Inhibiting the HIF-1α-SLUG Axis in Acute Respiratory Distress Syndrome

Abstract: The effective remission of acute respiratory distress syndrome- (ARDS-) caused pulmonary fibrosis determines the recovery of lung function. Inositol can relieve lung injuries induced by ARDS. However, the mechanism of myo-inositol in the development of ARDS is unclear, which limits its use in the clinic. We explored the role and mechanism of myo-inositol in the development of ARDS by using an in vitro lipopolysaccharide- (LPS-) established alveolar epithelial cell inflammation model and an in vivo ARDS mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…At the same time, we found that ITGA3 is closely related to EMT. On the one hand, several studies have found that EMT plays an important role in ARDS [ 15 , 16 ], on the other hand, ITGA3 has been confirmed to participate in the development process of tumors by participating in EMT in a variety of tumors [ 17 , 18 ]. We believe that it is meaningful to conduct subsequent experiments to specifically explore whether ITGA3 can play a role in the occurrence and development of ARDSp by participating in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we found that ITGA3 is closely related to EMT. On the one hand, several studies have found that EMT plays an important role in ARDS [ 15 , 16 ], on the other hand, ITGA3 has been confirmed to participate in the development process of tumors by participating in EMT in a variety of tumors [ 17 , 18 ]. We believe that it is meaningful to conduct subsequent experiments to specifically explore whether ITGA3 can play a role in the occurrence and development of ARDSp by participating in EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary brosis is highly associated with poor prognostic outcomes of ARDS patients [16][17][18]. Currently, there are no effective measures for anti-pulmonary brosis treatment [19][20]. The MSC-MVs have anti-pulmonary brosis effects, however, their speci c effects and mechanisms on ARDS pulmonary brosis have not been fully established [21].…”
Section: Discussionmentioning
confidence: 99%